Resistance of Neisseria Gonorrhoeae to Neutrophils - Johnson, M. Brittany; Criss, Alison K. (Frontiers in Microbiology, 2011)
Infection with the human-specific bacterial pathogen Neisseria gonorrhoeae triggers a potent, local inflammatory response driven by polymorphonuclear leukocytes (neutrophils or PMNs). PMNs are terminally differentiated phagocytic cells that are a vital component of the host innate immune response and are the first responders to bacterial and fungal infections. PMNs possess a diverse arsenal of components to combat microorganisms, including the production of reactive oxygen species and release of degradative enzymes and antimicrobial peptides. Despite numerous PMNs at the site of gonococcal infection, N. gonorrhoeae can be cultured from the PMN-rich exudates of individuals with acute gonorrhea, indicating that some bacteria resist killing by neutrophils. The contribution of PMNs to gonorrheal pathogenesis has been modeled in vivo by human male urethral challenge and murine female genital inoculation and in vitro using isolated primary PMNs or PMN-derived cell lines. These systems reveal that some gonococci survive and replicate within PMNs and suggest that gonococci defend themselves against PMNs in two ways: they express virulence factors that defend against PMNs’ oxidative and non-oxidative antimicrobial components, and they modulate the ability of PMNs to phagocytose gonococci and to release antimicrobial components. In this review, we will highlight the varied and complementary approaches used by N. gonorrhoeae to resist clearance by human PMNs, with an emphasis on gonococcal gene products that modulate bacterial-PMN interactions. Understanding how some gonococci survive exposure to PMNs will help guide future initiatives for combating gonorrheal disease.